The short-term toxicity of carbon nanotubes’ aqueous dispersion administered intravenously to rats - Igor E. Kuznetsov, Yuriy I. Gubin, Natalya D. Bunyatyan,, Oleg N. Kalugin, Sergiy M. Kovalenko, (Journal of Applied Pharmaceutical Science, 2023)
The biomedical application of carbon nanotubes (CNTs) is a dynamically developing area of scientific and industrial activity with high potential for the development of innovative tools for the diagnosis of diseases, targeted drug delivery, gene therapy, tissue engineering, immunomodulation, and theranostics. The inherent properties of CNTs, such as chemical inertness, high volume-to-surface ratio, mechanical rigidity, and ability to encapsulate both hydrophobic and hydrophilic substances and easily penetrate cell membranes, serve as the basis for the extensive development of supramolecular complexes for biomedical purposes, but on the other hand, they limit the use of CNTs in living organisms due to poor biocompatibility, the tendency to aggregation and accumulation, which leads to toxic effects. The results of numerous studies on the toxicity of CNTs performed over the past two decades have led to the understanding that the toxicity of CNTs, in general, depends on a set of their structural and physicochemical characteristics, which can be accurately measured and analyzed using appropriate laboratory instruments, but the interaction of specific CNTs with living organisms cannot be reliably predicted on the basis of such measurements and has to be experimentally investigated. Working on the project of a supramolecular nanocomplex for targeted delivery of doxorubicin to solid tumors, we faced the problem of the toxic effect of CNTs used as a vehicle. The general toxic effects and safety assessment of repeated intravenous administration of noncovalently functionalized multi-walled CNTs were studied in rats using a short-term (14 days) toxicity protocol. Repeated intravenous administration of an aqueous dispersion of MW CNTs did not have a noticeable effect on the state, behavior, and most of the hematological and biochemical parameters of animals, but some signs of liver dysfunction and activation of the immune system were found. At the same time, a microscopic examination of the autopsy material revealed noticeable ultrastructural changes in the lungs, liver, and hematopoietic organs. The results obtained were taken into account while planning further work on the project.
Keywords: Carbon nanotubes (CNTs), targeted drug delivery system, general toxic effects, short-term tox